PERSEPSI WISATAWAN MUSLIM TERHADAP WARUNG MAKAN MUSLIM YANG MENGGUNAKAN LOGO HALAL PERSPEKTIF EKONOMI SYARIAH DI KECAMATAN RANTEPAO KABUPATEN TORAJA UTARA - Khairil Fajri Rahim, Muh; Raehana, Syarifah; Bazith, Akhmad; Lawang, Hasanna; Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of halal logos in Muslim-owned restaurants serves as an important assurance of food halalness for Muslim tourists, particularly in tourist destinations with a predominantly non-Muslim population, such as Rantepao District, North Toraja Regency. This study aims to examine Muslim tourists' perceptions of the use of halal logos in Muslim-owned restaurants in Rantepao District, North Toraja Regency, and to analyze their use from the perspective of Islamic economics. This research employed a qualitative method with a descriptive approach. The study involved 10 informants, and the data were collected through interviews, observations, documentation, and literature review. The findings indicate that Muslim tourists have positive perceptions of the use of halal logos because they provide assurance of halal food, foster a sense of security and trust, and serve as one of the primary considerations when choosing a place to eat. From the perspective of Islamic economics, the use of halal logos reflects the implementation of the principles of honesty, trustworthiness (amanah), and transparency in business activities, thereby enhancing consumer confidence. In addition to its religious significance, the use of halal logos also provides economic benefits for business owners by increasing competitiveness and consumer trust, while offering certainty for Muslim tourists in consuming food that complies with Islamic law.